Construction estimate made easy - Tolarba, R. N. (Quezon City, Philippines : Sonny A. Mendoza Publishing, Inc., 1998)
Concrete as we know it today, had its beginning in 1824 when Joseph Aspdin took out a patent in England or "Portland" cement .
Chapter1. Concrete -- Chapter2. Masonry -- Chapter3. Metal Reinforcement -- Chapter4. Electrical Estimate -- Chapter5. Lumber -- Chapter6. Roofing -- Chapter7. Tile Work -- Chapter8. Staircase or Stairway -- Chapter9. Painting -- Chapter10. Labors Estimate -- Chapter 11. Definition of Terms.
Keywords: CONSTRUCTION